Pediatric health-related stress, coping and quality of life - Carona, Carlos (2014)
Objective – The aim of this study was twofold: first, to compare the experiences of health-related stress and the utilization of coping strategies between pediatric patients with different diagnoses and from distinct age-groups; and second, to examine the associations between the use of specific coping strategies and self-reported pediatric health-related quality of life. Materials and methods – 255 children/adolescents with a chronic health condition (asthma, epilepsy or cerebral palsy) were administered the Kidcope and the Disabkids-37 questionnaires. Chi-square tests and multivariate analyses of covariance were conducted to ascertain frequency and mean differences across clinical and developmental groups, and regression analyses were performed to examine associations between variables. Results – The experience of health-related stressors regarding physical limitation was more common for children/adolescents with asthma, while the occurrence of psychosocial stressors was more frequent in children/adolescents with cerebral palsy. There were differences in the utilization of coping strategies to deal with health-related stressors across diagnoses and agegroups, but the most frequently used strategies were consistently assessed as being the most effective. Externalizing emotional regulation was negatively related to the HRQL of pediatric patients with asthma and epilepsy, while self-criticism was negatively associated with the HRQL of children/adolescents with cerebral palsy. Conclusion – The experience of health-related stress, the utilization of coping strategies and their associations with pediatric HRQL are likely to vary across age-groups and diagnoses. Taking into account these developmental and clinical specificities is likely to improve the effectiveness of pediatric stress-coping assessments and interventions.